Sea Pollution in the Coastal Area: Problems and Challenges in Law Enforcement - Wijanarko, Frieda Pratiwi (Faculty of Law Universitas Negeri Semarang, 2022)
Natural resources must be guaranteed sustainability, among others, by maintaining the marine environment, marine pollution occurs due to heavy metals or plastic waste that scattered and household waste. The enforcement of environmental law against marine pollution can be seen in Law No. 32 of 2009 on Control of Environmental Management Number 51 Year 2004 regarding Sea Water Quality Standard explain about standard of quality of sea water can be said normal or contaminated. The problems that exist in this case is the analysis and solution to marine pollution in coastal areas in Jakarta Bay, Kali Baru, Cilincing North Jakarta. Environmental inhibiting factors pollution of coastal areas of the sea is the lack of human resources will be aware of the importance of safeguarding our oceans. Because we are without the sea is nothing because most of the food supply is from the sea e.g., fish or shell. Although there is now cultivation by using ponds as well but still many people choose sea fish because it is still considered fresh and not contaminated by harmful substances. The sea is a highway that connects all corners of the world. Many cities in Indonesia are in coastal areas that have great potential to make garbage or waste collisions.